Al-Taqdim wa Al-Ta’khir Pada Kalimat Qur’aniyyah: Satu Analisa dari Sudut Kesan Pada Makna Ayat-ayat Al-Qur’an - Hj. Mohd. Yusoff, Zulkifli (Jurnal Usuluddin, 1996)
Kalimat Qur’aniyyah is one of the important topics in the studies of l’jaz al-Qur’an. This article tries to look into and analyse the topic in terms of al-Taqdim and al-Ta’khir. According to Koran, there are many verses having a similar pattern but different in the al-Taqdim and al-Ta’khir which effect the meaning of the reases.